1H NMR studies on protein binding of histidine, tyrosine and phenylalanine in blood plasma. - Nicholson,JK; Gartland,KP (NMR Biomed, 1989)
The binding of histidine (His), phenylalanine (Phe) and tyrosine (Tyr) to macromolecules in blood plasma and serum has been investigated by high resolution 1H NMR spectroscopy. In single pulse and spin-echo spectra of quality control bovine serum and normal human plasma, there are no resonances in the chemical shift range to high frequency of delta = 5.3 ppm when measured in the pH (meter reading, uncorrected for the presence of 2H2O) range 3 to 8.5. On acidification of the plasma to pH less than 2.5, resonances from His and Phe are observable. In plasma from patients with Wilson's disease, weak signals from His and Tyr are seen in spin-echo spectra at pH 7.6, but increase in strength on acidification and signals from Phe appear at pH 1.8. Addition of standard solutions containing Tyr, His and especially Phe and Trp to plasma at neutral pH results in poor recovery of their expected signal intensity in spin-echo spectra. Addition of 2 M urea to bovine plasma at pH 4.5 results in the appearance of Phe signals. These data are consistent with Phe and Tyr (and to a lesser extent His) being bound in or to a macromolecular structure at neutral pH from which there is relatively slow exchange with the free solution environment. Experiments with model solutions suggest that serum albumin has a high capacity for binding aromatic amino acids (stabilized by hydrophobic interactions) at neutral pH and this is responsible for the NMR-invisibility of Tyr and Phe in blood plasma.